From icon of empire to national emblem: new evidence for the fallow deer of Barbuda - Perdikaris, Sophia; Bain, Allison; Baker, Karis; Grouard, Sandrine; Gonzalez, Edith; Hoelzel, A. Rus; Miller, Holly; Sykes, Naomi (Taylor & Francis, 2017)
Barbuda and Antigua's national animal is the fallow deer, Dama dama dama, a species native to the eastern Mediterranean that has been transported around the world by people during the last 8,000 years. The timing and circumstances by which fallow deer came to be established on Barbuda are currently uncertain but, by examining documentary, osteological and genetic evidence, this paper will consider the validity of existing theories. It will review the dynamics of human-Dama relationships from the 1500s AD to the present day and consider how the meaning attached to this species has changed through time: from a symbol of colonial authority and dominance, to a 'walking larder' after the slave emancipation of 1834, and now an important part of the island's economy and cultural heritage that requires careful management.